EFEKTIVITAS PENGGUNAAN METODE PEMBELAJARAN COURSE REVIEW HORAY BERBANTUAN ALAT PERAGA TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS II SMP DR. SOETOMO SURABAYA MATERI KESEBANGUNAN DAN KEKONGRUENAN (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2015)
The purpose of this study was to determine the mistakes made and the difficulties experienced by students Autism  class V SDN Inclusion Mojo III Surabaya. Besides, the purpose of this study also want to know the causes and solution . From the analysis of the data obtained the following conclusion: The percentage of errors made autistic student class V SDN Mojo III Surabaya in solving mathematical word problems on the subject of the Commission and the FPB Based on the analysis of the test results , the proportion of students' mistakes in solving math story that is 33 , 3 % misconception , 25 % fault Procedure 41.7 % technical error . From the percentage shown that a large proportion of most errors are technical errors. The percentage of the difficulties experienced by children with autism , a class V SDN mojo III Surabaya in doing math story problems is 33.3 % of students with autism have difficulty dyslexia, 33.3 % of students with autism have difficulty dysgraphia, and 33.3 % of students with autism have difficulty dyscalculia